Contrastive Principle of Phonomatic Segmentation of the Chinese Language (Proceedings of Southern Federal University. Philology, 2017)
Alexander D. Petrenko, Danuta M. Khrabskova (Simferopol, Crimean Republic)The formation of the noospheric universe predetermines the convergent type of scientific thinking, as well as the use of the principle of apperception in the process of cognition. Thus, the comparative method becomes one of the most universal, since it allows to typologize a significant amount of information and often fragmented information. Action by analogy, transferred from the practical to the theoretical plane, is one of the main factors ensuring the scientific reliability of the results of the phonemic division of the Chinese language, the segment units of which are established in the process of contrastive analysis according to the opposition method with the standard.Key words: comparative method, contrastive linguistics, phoneme, syllabem, sound representation, distinctive feature.DOI 10.23683/1995-0640-2017-3-153-164